Optimization design of heat dissipation structure of inserts supporting run-flat tire. (December 2019) - Zang, Liguo; Cai, Yizhang; Wang, Baosheng; Yin, Rongdong; Lin, Fen; Hang, Peng
Inserts supporting run-flat tire is a key technology in the field of vehicle active safety. When the vehicle is under zero driving condition, the deformation of the inserts supporting run-flat tire due to compression can cause the tire to be crushed, and loss of adhesion between the tire and rim can lead to separation. These situations can reduce the cruising ability of the vehicle. Under zero driving condition, the insert, which is the main support body for the tire, could rub against the inner part of the tire sharply, thereby generating heat in the tire. Heat in the tire is difficult to dissipate and can accumulate rapidly under this condition. As the temperature of the tire and insert increases, the inserts supporting run-flat tire could fail to support the vehicle. To improve heat dissipation of the insert, a finite element model of the inserts supporting run-flat tire under the condition of zero rolling is established. The steady-state temperature field of the inserts supporting run-flat tire is analyzed using ANSYS Workbench. The insert temperature field and heat flux are solved. The optimization design of axial heat dissipation holes and surface heat dissipation grooves based on experimental and simulation results of the insert is presented. Finally, the optimization structure of the insert is verified using a thermal–mechanical coupling simulation method. The conclusions are of great significance for optimizing inserts supporting run-flat tire and improving zero rolling ability of tire.